Implementation of Disaster-Resilient Village (DESTANA) Principles Based on Local Wisdom - Ani Susanti; Irwan Waris; Irwansyah Kamindang; Darwis; Muhammad Afandi (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
This study aims to explore how the principles of the Disaster-Resilient Village (DESTANA) program are implemented in Bolapapu Village through the integration of local wisdom, as well as to examine how such integration enhances community resilience across different phases of disaster management.This research employed a qualitative design. Data were collected in 2025 through in-depth interviews with 20 informants consisting of village officials, traditional leaders, disaster volunteers, and affected households; participatory observation of disaster preparedness activities and traditional rituals; and document analysis of local regulations, disaster reports, and customary norms. Data analysis followed the Miles and Huberman model, with triangulation applied to ensure validity. The findings reveal four DESTANA principles implemented as efforts to prevent and manage disasters in Bolapapu Village: participation, self-reliance, mutual cooperation, and sustainability. These principles are operationalized through local wisdom practices such as pahombo (communal labor), nosimpali (solidarity and reciprocal relations), and traditional ecological knowledge (reading natural signs). These practices enhance preparedness through early warning mechanisms, accelerate response, facilitate recovery through internal community mobilization, and encourage adaptive customary norms for long-term resilience. This study contributes empirical evidence to the discourse on hybrid resilience by integrating formal disaster risk reduction frameworks with local knowledge systems. The Bolapapu model may serve as a reference for other disaster-prone villages in Indonesia and globally, particularly in regions where customary institutions remain strong.